Inhaled Antibiotics for Mycobacterial Lung Disease - Brandon Banaschewski; Thomas Hofmann (MDPI AG, 2019)
Mycobacterial lung diseases are an increasing global health concern. Tuberculosis and nontuberculous mycobacteria differ in disease severity, epidemiology, and treatment strategies, but there are also a number of similarities. Pathophysiology and disease progression appear to be relatively similar between these two clinical diagnoses, and as a result these difficult to treat pulmonary infections often require similarly extensive treatment durations of multiple systemic drugs. In an effort to improve treatment outcomes for all mycobacterial lung diseases, a significant body of research has investigated the use of inhaled antibiotics. This review discusses previous research into inhaled development programs, as well as ongoing research of inhaled therapies for both nontuberculous mycobacterial lung disease, and tuberculosis. Due to the similarities between the causative agents, this review will also discuss the potential cross-fertilization of development programs between these similar-yet-different diseases. Finally, we will discuss some of the perceived difficulties in developing a clinically utilized inhaled antibiotic for mycobacterial diseases, and potential arguments in favor of the approach.